Committing a Crime while Intoxicated: The Basis of Liability and Legal Regulation - Bezugly, Sergej N.; Bazarov, Rustam A.; Kostennikova, Elizaveta I.; Lesnikov, Gennadij Yu.; Mironuk, Ivan V. (International Journal of Criminology and Sociology, 2022)
Alcohol and drugs have been known for a long time, and their purpose has changed in the course of history. Being part of the global culture, they have come down to us. With the development of mankind, drugs were limited. This article attempts to analyzes the concept and types of intoxication. The authors also take into consideration the basis of criminal liability for committing a crime while intoxicated, as well as the role of intoxication in criminal law. This research was based on a dialectical approach to the disclosure of legal phenomena and processes using general scientific (systematic and logical methods, analysis and synthesis) and specific scientific methods. In the end, It can be concluded that the state of intoxication can be included in the main corpus delict, used as a qualifying attribute, as well as circumstances aggravating liability. It is indicated that considering intoxication as an aggravating circumstance requires a connection between crime and intoxication.